Association Between Culture-Negative Versus Culture-Positive Sepsis and Outcomes of Patients Admitted to the Pediatric Intensive Care Unit - Hazwani, Tarek R (Cureus, 2020)
Background Sepsis remains a major cause of death, with high mortality and morbidity rates in children. The cause of mortality may be associated with several factors, including differences in cultures and the type of organism. This study was aimed at evaluating the characteristics and outcomes of negative bacterial blood culture compared to those of positive bacterial blood culture in children with severe sepsis/septic shock. Methods A retrospective cohort study was conducted at a pediatric intensive care unit (PICU) of a tertiary care medical center. All pediatric patients, from newborn to 14 years of age, admitted between April 2015 and January 2018 were included in the study if they fulfilled the criteria for severe sepsis/septic shock. Results Of the 209 patients, 30 (14.3%) had a positive bacterial blood culture whereas 179 (86.6%) had a negative bacterial blood culture. Mortality was more in positive bacterial blood culture 13 (43%) vs 35 (20%) in negative bacterial blood culture (P = 0.004). Respiratory tract infections were extremely common, present in 108 of 179 (60%) patients, and tended to result in a negative culture. The rate of organ dysfunction was higher in the positive bacterial blood culture group at admission (P = 0.01). However, the results did not reveal a significant finding related to multiorgan dysfunction syndrome (MODS) progression over three days of PICU admission (P = 0.06). Conclusion The negative bacterial blood culture constitutes a substantial proportion of pediatric patients with severe sepsis/septic shock. Furthermore, these pediatric patients have a lower mortality rate compared to positive bacterial blood cultures. The culture-negative sepsis group also had less organ dysfunction.